Hesperis burdurensis (Brassicaceae), a new species from Southwest Anatolia - Çeti̇n, Özlem (Phytotaxa, 2022)
A new species, Hesperis burdurensis (Brassicaceae), from southwest Anatolia is described and illustrated. The species is similar to Hesperis tosyaensis and H. pisidica but distinguished from these species by its leaf shape, petal size, and trichome features. Herein, an identification key with a description of the new species is provided. Scanning electron microscope (SEM) observations of pollen grains and trichome types are presented. Comments on the habitat, ecology, phenology, distribution, and conservation status of the new species are also provided.